2016
DOI: 10.1371/journal.pone.0155994
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Liver Transaminases and Dyslipidaemia among 2-10 y.o. Northern Mexican Children

Abstract: Background and AimsThe increase in overweight and obese children may be linked to increased rates of liver damage and dyslipidaemia. This study aimed to explore the associations of liver biomarkers with overweight/obesity and dyslipidaemia in Mexican children.MethodsThe study was a population-based cross-sectional nutritional survey carried out in the State of Nuevo León, Mexico. The study included a 414 subjects aged between 2 and 10 years old (47.8% girls) who took part in the State Survey of Nutrition and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(43 reference statements)
0
3
0
1
Order By: Relevance
“…While pediatric NAFLD has been positively associated with atherogenic lipid components in the general population [ 44 47 ], study on this association in children and adolescents with obesity demonstrated diverging results [ 15 , 21 , 23 , 48 ]. A hospital-based study indicated association between NAFLD and dyslipidemia [ 48 ], while a large population-based study did not detect such association [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…While pediatric NAFLD has been positively associated with atherogenic lipid components in the general population [ 44 47 ], study on this association in children and adolescents with obesity demonstrated diverging results [ 15 , 21 , 23 , 48 ]. A hospital-based study indicated association between NAFLD and dyslipidemia [ 48 ], while a large population-based study did not detect such association [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a Canadian study, the cutoff value for ALT was suggested to be 30 mg/dl in children between 1 and 12 years of age and 24 mg/dl in those between 13 and 19 years 11 . In other regions, including Europe 12 , 13 , the United Kingdom 14 , Mexico 15 , Sweden 16 , Iran 17 , Taiwan 18 and China 19 , the reference ranges of liver enzymes in children were evaluated in a similar manner. However, in Korean children and adolescents, the similar studies were not population-based, and the association with MetS was not analyzed 20 or adult data 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a Canadian study, the cutoff value for ALT was suggested to be 30 mg/dl in children between 1 and 12 years of age and 24 mg/dl in those between 13 and 19 years 9 . In other regions, including Europe 10,11 , the United Kingdom 12 , Mexico 13 , Sweden 14 , Iran 15 , Taiwan 16 and China 17 , the reference ranges of liver enzymes in children were evaluated in a similar manner. However, in Korean children and adolescents, the similar studies were not populationbased, and the association with metabolic syndrome was not analyzed 18 or adult data 19 .…”
Section: Introductionmentioning
confidence: 99%